Determinanty zmiany systemu wyborczego - Wojtasik, Waldemar (Political Preferences, 2016)
The Determinants of Electoral System Change Elections are a tool for the competing entities to achieve political goals. Therefore, electoral procedures are a significant element affecting their political perspectives. A change in the electoral system depends on balance of power in the parliament. In practice, two models of electoral reforms are possible. In the first of them, political parties collaborate to reform the system. Thus, they protect the interests of as many parties as possible. In the second one, the majority can force others to accept the solutions that are beneficial for them. The majority promote the institutional patterns and procedures that give them a chance to consolidate or increase the relative power of influence of elections. The presented paper includes the analysis of social preferences concerning a reform of the electoral system in Poland. The study revealed the preference for the cooperative model of changing the electoral system. Only the respondents who identified themselves as having right-wing inclinations approved of the competitive model. Key words: change of the electoral system, electoral system in Poland, electoral crisis, reforms of the election law